An Investigation of the Average Bid Mechanism for Procurement Auctions - Chang, Wei-Shiun; Chen, Bo; Salmon, Timothy C. (Management Science, 2015)
In a procurement context, it can be quite costly for a buyer when the winning seller underestimates the cost of a project and then defaults on the project midway through completion. The average bid auction is one mechanism intended to help address this problem. This format involves awarding the contract to the bidder who has bid closest to the average of the bids submitted. We compare the performance of this mechanism with the standard low price mechanism to determine how successful the average bid format is in preventing bidder losses as well as its impact on the price paid by the buyer. We find the average bid mechanism to be more successful than expected because, surprisingly, bidding behavior remains similar between the average bid and low price auctions. We provide an explanation for the bidding behavior in the average bid auction that is based on subjects having problems processing signals near the extremes of the distribution. This paper was accepted by Teck-Hua Ho, behavioral economics.